Pengembangan E-LKPD Berbasis Problem Based Learning Berbantuan Liveworksheets untuk Meningkatkan Hasil Belajar Siswa pada Materi Energi dan Usaha Di SMA Negeri 17 Medan - Welki Bahri Sigiro; Jonny Haratua Panggabean (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The aim of this study is to develop teaching materials in the form of Problem-Based Learning (PBL)-based E-LKPDs supported by Liveworksheets to improve student learning outcomes in the subject of Energy and Work. This study is a Research and Development (R&D) using the ADDIE development model. During the development phase of the ADDIE model, the E-LKPD was validated by subject matter experts and media experts to assess its suitability. It was also evaluated by teachers and tested in a small pilot group to assess its practicality. During the implementation phase, the E-LKPD was used in the learning process, beginning with a pre-test and concluding with a post-test. The results of the pre-test and post-test were used in the evaluation stage to determine effectiveness using the N-Gain. This research produced an E-LKPD with a feasibility validation result of 88.89% from subject matter experts, categorised as feasible, and 93.75% from media experts, also categorised as feasible. The practicality of the E-LKPD, as assessed by teachers, achieved a score of 98.33%, classified as practical, whilst the small-group pilot test yielded a score of 95.94%, also classified as practical. Effectiveness was determined by the N-Gain test, which yielded a score of 0.73, classified as high. This indicates that the developed E-LKPD can improve students’ learning outcomes in the subject of energy and work.